The Establishment of Tax on Land and Building Rights (BPHTB) - Karmani Karmani; Widayati Widayati (Sultan Agung Notary Law Review, 2021)
This study aims to examine the implementation of the collection of Customs Tax on Land and Building Rights in Boyolali Regency. Reviewing the obstacles that arise in the implementation of the collection of Customs Tax on Land and Building Rights in Boyolali Regency. Reviewing solutions in overcoming the obstacles that arise in the implementation of the collection of Customs Tax on Land and Building Rights in Boyolali Regency. This research is a sociological juridical research. The results of the study concluded that mHowever, there is a discrepancy with the laws and regulations in the implementation of the collection of Duties on the Acquisition of Rights to Land and Buildings in Boyolali Regency, namely when there is a transfer of rights to land and buildings due to a sale and purchase whose transaction value is lower than the market price, the transaction value will be determined by the BPPKAD officer based on market prices and surveys of the tax object in question, even though the provisions of Article 87 paragraph 2 of Act No. 28 of 2009 and Article 7 of Boyolali Regency Regulation Number 2 of 2011 state that the basis for imposing BPHTB taxes on the acquisition of buying and selling rights with lower transaction value rather than the market price, the basis for the imposition of BPHTB tax is the Tax Object Sales Value (NJOP) of Land and Building Tax. In the collection process there are still some obstacles, namely the lack of knowledge of taxpayers regarding information and socialization of the regulations on the Acquisition of Rights on Land and Buildings, as well as the limited number of Human Resources (HR) from the Office of the Regional Financial and Asset Management Revenue Agency of Boyolali Regency, even though the area and number of transfers of land and buildings is small in Boyolali Regency is high, thus interfering with the performance of the Land Deed Maker Officials and the National Land Agency in terms of land registration. There is a need for periodic socialization regarding the Customs for Acquisition of Land and Building Rights by the Regional Government, while the problem of uncertified land requires cooperation with the local National Land Agency, for example conducting a prona program.